PENGEMBANGAN SISTEM SELEKSI PENERIMAAN CALON SISWA BARU DENGAN METODE SIMPLE ADDITIVE WEIGHTING - Jenit Erga Falabitsa; Lelah Lelah (Teknik Informatika, 2020)
Selection is the process of selecting candidates who meet the requirements or standards that have been set. One of them is in the educational institutions in the selection of New Student Admissions, in the selection of new student data must be precise, this time the Study discusses the case in the Vocational High School State 1 Cibadak, is still using the manual system using Microsoft Excel applications in new student selection, this caused new student data to be incorrect so that the committee was overwhelmed in ranking the ranking. Making new student selection Information System using the Simple Additive Weighting (SAW) method facilitates the committee and prospective students in registering and processing grades data because with the SAW method the value processing has been automatically ranked based on the highest grade and the decision received or not received by students can be seen.